Attitudes toward older women and men – generational differences - Finogenow, Maria (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
The aim of the study was to analyze the differences in attitudes toward aging of men and women in a group of young adults and seniors. Moreover the sex of the participants was controlled. The total sample consisted of 128 participants. The results show that the young adults show more positive attitude to elderly than the old adults. Moreover the results indicate that the attitude toward aging of men and women depends on the evaluated area, sex and age of the participants.